2018
DOI: 10.1093/nar/gky721
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA expression in human hematopoietic cells is widespread and cell-type specific

Abstract: Hematopoietic stem cells differentiate into a broad range of specialized blood cells. This process is tightly regulated and depends on transcription factors, micro-RNAs, and long non-coding RNAs. Recently, also circular RNA (circRNA) were found to regulate cellular processes. Their expression pattern and their identity is however less well defined. Here, we provide the first comprehensive analysis of circRNA expression in human hematopoietic progenitors, and in differentiated lymphoid and myeloid cells. We her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
91
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(104 citation statements)
references
References 59 publications
13
91
0
Order By: Relevance
“…For example, approximately 15,000 circRNAs are expressed in both human and mouse orthologous loci, representing approximately 15% and 40% of the total cir-cRNAs in humans and mice, respectively [40]. (4) Specificity: in terms of cell type, tissue or developmental stage, circRNAs often show specific expression [41][42][43][44].…”
Section: Circrnasmentioning
confidence: 99%
“…For example, approximately 15,000 circRNAs are expressed in both human and mouse orthologous loci, representing approximately 15% and 40% of the total cir-cRNAs in humans and mice, respectively [40]. (4) Specificity: in terms of cell type, tissue or developmental stage, circRNAs often show specific expression [41][42][43][44].…”
Section: Circrnasmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are a class of covalently closed single-stranded RNA molecules whose 3′ and 5′ ends are linked by a back-splice event ( 6 ). Some of them have been proven to be structurally stable ( 7 ), tissue and cell specific ( 8 ), abundantly expressed in various tissues and cells ( 9 ), and evolutionarily conserved ( 10 ). Emerging evidence has shown that some circRNAs are involved in many biological processes and a variety of human diseases, including innate immunity ( 11 ), inflammation ( 12 ), tumorigenesis ( 13 , 14 ), aging ( 15 ), diabetes mellitus ( 16 ), neurological disorders ( 17 ), and cardiovascular diseases ( 18 ) by acting as microRNA (miRNA) sponges ( 19 21 ), regulating splicing and transcription ( 22 , 23 ), interacting with RNA-binding proteins ( 24 , 25 ), or serving as protein translation templates ( 26 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Next Generation Sequencing (NGS) recently showed a conspicuous circRNA expression in human hematopoietic progenitors, and in differentiated lymphoid and myeloid cells (Nicolet et al, 2018). In the hematopoietic compartment, circRNAs are significantly enriched and secreted in vesicles named exosomes derived from platelets, where circRNAs resulted to be more abundant and widely expressed compared with other cell types (Preußer et al, 2018).…”
Section: Circrnas In Hematopoiesismentioning
confidence: 99%
“…In the hematopoietic system, circRNA expression is cell-type specific, and it increases upon cell maturation. CircRNA splicing variants can also be cell-type specific (Nicolet et al, 2018). In the bone marrow, the hematopoietic stem cells (HSCs) differentiate into various progenitor cells, which in turn generate many types of myeloid and lymphoid cells requiring a tight regulation of gene expression of transcription factors and non-coding RNAs (Goode et al, 2016).…”
Section: Circrnas In Hematopoiesismentioning
confidence: 99%